6h+5=4h-17

Simple and best practice solution for 6h+5=4h-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6h+5=4h-17 equation:


Simplifying
6h + 5 = 4h + -17

Reorder the terms:
5 + 6h = 4h + -17

Reorder the terms:
5 + 6h = -17 + 4h

Solving
5 + 6h = -17 + 4h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4h' to each side of the equation.
5 + 6h + -4h = -17 + 4h + -4h

Combine like terms: 6h + -4h = 2h
5 + 2h = -17 + 4h + -4h

Combine like terms: 4h + -4h = 0
5 + 2h = -17 + 0
5 + 2h = -17

Add '-5' to each side of the equation.
5 + -5 + 2h = -17 + -5

Combine like terms: 5 + -5 = 0
0 + 2h = -17 + -5
2h = -17 + -5

Combine like terms: -17 + -5 = -22
2h = -22

Divide each side by '2'.
h = -11

Simplifying
h = -11

See similar equations:

| 2w-2x-y+7w+15x-5y= | | 124-3x=6x+16 | | 11x-3y+13w+3y-4w+2x= | | 6w+9y+5x+8x-15y+4w= | | 2a+3(a-7)=a+3 | | 4(2x-5)=3(8-x) | | 4w+6x-13y+5w+7x+7y= | | 10n+7=107 | | 16a+17b+2c+2c-4b-3a= | | 2i+7=5i-2 | | 11p+19q+p-3q-6p= | | 3(2x-5)=27 | | x+(x+6)+12=66 | | 71-2x=34x+23 | | 14m+6n-4m+7n= | | (x+6)+12=66 | | 14-7x=110-35x | | 6a+1=2a+25 | | X^2-71*x+72=0 | | 2x+3=19+x | | -26-7x=110-35x | | -3x^2=-12 | | 180-7x=20x+21 | | 9t-3=8t-18 | | 7y+3=12y+8 | | -155-7x=10x+15 | | -155-7x=10x+25 | | 18+4y=18 | | 8x^2+3x+10=0 | | 6n-7=3n+2 | | 5x-18=22 | | 3x+7x=8 |

Equations solver categories